Association of trabecular bone score corrected for tissue thickness with glucose metabolism in acromegaly - Kužma, Martin; Vaňuga, Peter; Pávai, Dušan; Killinger, Zdenko; Hans, Didier; Binkley, Neil; Payer, Juraj; Jackuliak, Peter (Frontiers in Endocrinology, 2024)
Acromegaly is associated with increased vertebral fracture (VF) risk regardless of bone mineral density (BMD). However, the vertebral trabecular compartment is still low; a possible contributor to this may be impaired glucose metabolism (GM) which frequently complicates acromegaly. Additionally, soft tissue thickness may confound bone imaging in acromegaly patients.Objectives To assess the association of GM with bone mineral density (BMD), trabecular bone score adjusted for BMI (TBSBMI), and for tissue thickness (TBSTT) among acromegaly subjects.Patients and methods: Cross-sectional study was performed of 70 consecutive acromegaly patients (24 males/46 females, aged 55.1 years) divided in two subgroups: abnormal GM (n=35) and normal GM (n=35). Using DXA, BMD, TBSBMI, TBSTT and VF screening was performed.Results: In all subjects, TBSTT was higher (mean 9.5%) than TBSBMI. Abnormal GM subjects had lower TBSBMI (1.166±0.15) than normal GM subjects (1.232±0.12; p<0.05). No between-group difference in TBSTT or BMD was observed. In a multiple regression model, the best predictor of TBSTT was HbA1c (p=.002). None of the DXA measures or GM parameters was significant predictor of VF (n=7).Abnormal GM acromegaly subjects had lower TBSBMI than those with normal GM.TBSTT wash higher than TBSBMI and no between-group difference based on GM status was observed TBSTT was significantly associated with GM parameters, notably HbA1c. The relationship of TBSTT with GM parameters may imply an effect of GM on trabecular bone microstructure in patients with acromegaly; further study is indicated.